Serum osteoprotegerin (OPG) levels are associated with disease progression and response to androgen ablation in patients with prostate cancer. - Eaton, C; Wells, J; Holen, I; Croucher, P; Hamdy, F (2004)
BACKGROUND: Osteoprotegerin (OPG) is a tumour and/or bone derived factor that may protect tumour cells from apoptosis. In this study, we have measured serum OPG levels in untreated prostate cancer patients with advanced prostate cancer compared to patients with organ confined disease and in treated patients receiving androgen ablation. METHODS: Serum OPG levels were measured by ELISA in samples collected from 104 patients with either newly diagnosed (n = 59) or advanced prostate cancer treated by androgen ablation (n = 45) and compared with levels in serum from patients with benign prostatic hyperplasia (BPH) (n = 10) and young healthy men (n = 10). RESULTS: Untreated patients with locally advanced disease had significantly higher OPG levels than those with organ confined disease. Patients with advanced disease responding to androgen ablation (serum PSA < 1 ng/ml) had serum OPG levels that were significantly lower than those with clinically progressing disease (PSA > 10 ng/ml). OPG levels in the latter were not significantly different from levels in patients with early signs of biochemical progression (PSA >1 but <10 ng/ml). CONCLUSIONS: OPG is a potential new marker, which is elevated in the serum of patients with advanced prostate cancer and may be an indicator of early disease progression.